Analysis of the Needs for Developing Reaching Materials Based on Alternative Energy ICT Integrated with Ethno-PBL to Facilitate Students’ Knowledge and Creative Thinking Skills - Merindi, Merindi Putri Islami; Asrizal; Hidayati; Hayyu Yumna (Universitas Mandiri, 2025)
This study aims to design teaching materials that combine ICT and cover the topics of alternative energy, as well as ethno-PBL. The main purpose of creating these teaching materials is to help students understand better and improve their knowledge and creative thinking skills. This study uses descriptive statistical analysis, with data collected through questionnaires, student daily test scores and performance assessments. This study revealed five main findings from the needs analysis including; First, the context analysis of teaching materials for physics learning is still low, with an average score of 42.5. Second, the use of local science in the material is still low, with an average of 40. Third, it shows that the PBL model is not well integrated in the teaching materials, with an average of 48. Fourth, it shows that students' ability to understand the material is still lacking with an average of 34.22. Fifth, creative thinking skills are also still low, with an average of 34.61. The results obtained indicate that the development of ICT-based teaching materials integrated with Ethno-PBL is very much needed by teachers and students to improve students' knowledge and creative thinking skills.